Cost-utility of focused ultrasound compared to radiotherapy for Dutch patients with uncomplicated non-spinal bone metastases - Galendi, Julia Simões Corrêa; Nijholt, Ingrid; Hovenier, Renée; Slotman, Jorik; Phernambucq, Erik; Stock, Stephanie; Bos, Clemens; Braat, Manon; Verkooijen, Helena; Boomsma, Martijn; Müller, Dirk (Springer Nature, 2025)
IntroductionNon-randomized clinical trial has shown that Magnetic Resonance guided High-intensity focused ultrasound (MR-HIFU) leads to faster pain relief compared to the current standard of care External Beam Radiotherapy (EBRT). ObjectiveTo evaluate the cost-utility of ’early MR-HIFU’ (with optional EBRT afterwards) or ‘delayed MR-HIFU’ (i.e., MR-HIFU after failed EBRT) versus EBRT (with optional re-irradiation with EBRT) from the societal perspective in the NetherlandsMethodsA lifelong patient-level simulation model was developed. After a treatment with either MR-HIFU or EBRT, a patient could have: (i) complete pain relief, (ii) partial pain relief, (iii) persistent pain and (iv) death. We also accounted for the event of a pathological fracture. Model outputs were costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICER). The net monetary benefit was calculated considering the willingness-to-pay threshold of €80,000 per QALY gained, adjusted by the Dutch disease severity index. Deterministic and probabilistic sensitivity analyses were conducted. ResultsThe strategy ‘delayed MR-HIFU’ costs €706 more than EBRT, whilst ‘early MR-HIFU’ costs €1,875 more than EBRT.‘Early MR-HIFU’ adds 0,15 more QALYs than EBRT, resulting in an ICER of €12.755 per QALY and an incremental net monetary benefit of €8,631. At a threshold of 80,000€ per QALY there is a 77% probability that ‘early MR-HIFU’ is the most cost-effective option.ConclusionAlthough there are still uncertainties relating to implementation of MR-HIFU in patient care, our modelling study shows that offering MR-HIFU as an early treatment would be the most cost-effective option in the Netherlands.